Clinical use of blinatumomab for B-cell acute lymphoblastic leukemia in adults - Lee KJ; Chow V; Weissman A; Tulpule S; Aldoss I; Akhtari M (Dove Medical Press, 2016)
Kum Ja Lee,1 Vivian Chow,1 Ashley Weissman,2 Sunil Tulpule,3 Ibrahim Aldoss,4 Mojtaba Akhtari5 1Department of Clinical Pharmacy and Pharmaceutical Economics and Policy, University of Southern California, 2Department of Pharmacy, University of Southern California Norris Cancer Hospital, Los Angeles, CA, 3Department of Medicine, Raritan Bay Medical Center, Perth Amboy, NJ, 4Department of Hematology and Hematopoietic Cell Transplantation, City of Hope, Duarte, CA, 5Jane Anne Nohl Division of Hematology and Center for the Study of Blood Diseases, University of Southern California Norris Comprehensive Cancer Center, Los Angeles, CA, USA Abstract: Adults with relapsed or refractory B-cell acute lymphoblastic leukemia have a dismal prognosis with a short median overall survival that can be measured in months. Because most patients will have chemotherapy-resistant disease, allogeneic hematopoietic stem cell transplantation remains the only potentially curative treatment. Despite advances in current management, patients continue to have poor outcomes and lack of durable responses. Thus, new therapies with alternative modes of actions are currently being investigated. Blinatumomab is a novel bispecific T-cell engager that simultaneously binds CD3-positive cytotoxic T-cells and CD19-positive B-cells, resulting in selective lysis of tumor cells. It has shown promising results in patients with relapsed or refractory acute lymphoblastic leukemia or those achieving hematologic response with persistent minimum residual disease. Future clinical trials will answer questions regarding its optimal place in the treatment paradigm. Dose-limiting toxicities include immunological toxicities and cytokine release syndrome. However, most patients tolerate the therapy relatively well. This review will focus on the pharmacology, clinical efficacy, and safety of blinatumomab in the treatment of adult B-cell acute lymphoblastic leukemia while highlighting its unique drug warnings and toxicity management. Keywords: ALL, relapsed/refractory, BiTE, BLINCYTO